“Outside the industry, nobody knows what we do” SEO as seen by search engine optimizers and content providers - Sebastian Schultheiß and Dirk Lewandowski (Journal of documentation, 2020)
In commercial web search engine results rankings, four stakeholder groups are involved: search engine providers, users, content providers, and search engine optimizers. Search engine optimization (SEO) is a multi-billion-dollar industry and responsible for making content visible through search engines. Despite this importance, little is known about its role in the interaction of the stakeholder groups. We conducted expert interviews with 15 German search engine optimizers and content providers, the latter represented by content managers and online journalists. The interviewees were asked about their perspectives on SEO and how they assess the views of users about SEO. SEO was considered necessary for content providers to ensure visibility, which is why dependencies between both stakeholder groups have evolved. Despite its importance, SEO was seen as largely unknown to users. Therefore, it is assumed that users cannot realistically assess the impact SEO has, and that user opinions about SEO depend heavily on their knowledge of the topic. This study investigated search engine optimization from the perspective of those involved in the optimization business: content providers, online journalists and search engine optimization professionals. The study therefore contributes to a more nuanced view on and a deeper understanding of the SEO domain.